Memahami Pemelajaran Menerusi Penyelidikan Fenomenografi - Wan Ali, Wan Zah (Universiti Putra Malaysia Press, 1995)
This paper tries to focus attention to the fact that learning should be studied from the students' perspective. In this way the learning phenomena could be better described in detail and learning problems could probably be solved in a more meaningful manner. To achieve this objective, one research study on qualitative differences in learning outcome approach is cited to explain phenomenography.